Lather, Powders, Soaps: Hygiene Materials in the Advertising Imagery - Costanzo , Giorgia (E|C, 2023)
Through the observation of a corpus of cleaning products’ commercials – especially detergents –, the aim of the following paper is to examine if and how the material transformations inscribed in the removal of dirt contribute to the shaping of values such as purity and contamination. This work starts from the point of view of the anthropologist Mary Douglas’s idea of dirt as disorder but also from the assumption that common sense and every day practises allow Semiotics to explicit proliferations of meaning that circulate in our culture. In this sense, the research hypothesises that there are logics of cleanliness in the struggle against dirt staged by advertising, that are linked both to the materiality and consistency of dirt and to the forms of removal of impurities.